Spatial analysis approach for sustainability of campus radio in Malaysia: Case study of UMS KKFM campus radio - Oliver Valentine Eboy; Syahruddin Ag Ahmad; Lizalin Kalang; Kong Teck Sieng (IOP Publishing Ltd., 2022)
The campus radio in Malaysia usually established for educational purpose which is important for the student’s development in soft skills. Unfortunately, some campus radio is regarded as not popular and irrelevant due to the emergence of the Internet. Thus, this leads to low utilization of campus radio among students and the public. Although, there are listeners to the campus radio but it is difficult to identify the distribution pattern especially the location of the listeners. Therefore, this study was conducted using spatial analysis to determine the distribution pattern of radio listeners specifically towards campus radio in Universiti Malaysia Sabah (UMS) KKFM. The study was based on the perceptions of the respondents reside around the area of UMS with distance within 15km. Techniques such as interpolation, hotspot and geographic distribution measurement were applied in this study using ArcGIS software. Based on the result, the spatial pattern shows that the public and those reside far from UMS are among the regular listeners of the campus radio. Finally, the outcome of this study indicates that the campus radio is still relevant specifically for certain programmes. This study is important for service improvement and to achieve sustainability of the campus radio.